Scientific Instruments Committee - Planning Commission (Planning Commission, Government of India, 1958)
The First Report of the Scientific Instruments Committee submitted to the Planning Commission of the Government of India in 1958 presents a comprehensive framework for developing the indigenous production of scientific instruments to support the country’s growing needs in education, research, and industrial development. Recognizing the heavy dependence on imported instruments and the limited domestic manufacturing capacity, the report emphasizes the urgent need for coordinated national efforts to establish a sustainable scientific instruments industry in India. A central recommendation is the creation of a dedicated Central Agency, as proposed by the Council of Scientific and Industrial Research, to coordinate the promotion, development, and production of scientific instruments while facilitating collaboration among various ministries, research institutions, and industrial sectors. The committee highlights the importance of conducting systematic surveys to assess the present and future demand for scientific instruments across teaching institutions, research laboratories, and industrial establishments, enabling the formulation of a phased development program over the coming decade. The report also advocates expanding the production capabilities of the private sector and promoting the standardization of designs for approximately 200 to 250 commonly used instruments to ensure uniform quality and facilitate procurement by educational institutions. Strengthening the role of the Indian Standards Institution in establishing technical specifications and certification processes is recommended to enhance quality control and build confidence in domestically produced instruments. In addition, the report stresses the need for specialized training programs for technicians and engineers involved in the manufacturing, maintenance, and repair of scientific instruments, suggesting collaboration with educational institutions and the introduction of dedicated courses in instrument technology. To accelerate technological advancement, the committee encourages foreign collaborations through international technical assistance programs that would enable knowledge transfer and access to advanced manufacturing practices. The preparation of a comprehensive national directory of scientific instruments produced within India is also recommended to improve awareness of domestic capabilities and encourage local procurement. Overall, the report outlines a strategic roadmap aimed at reducing reliance on imports, strengthening domestic manufacturing capacity, and building a self-reliant ecosystem for scientific instrument production that supports India’s scientific, educational, and industrial progress.
Planning Commission Government of India New Delhi, 1958
Keywords: Scientific Instruments Development; Scientific Instruments Committee; Indigenous Manufacturing; Central Agency for Instruments; Scientific Instrument Standardization; Industrial Research Support; Indian Standards Institution; Instrument Technology Training; Foreign Technical Collaboration; Scientific Instrument Directory; Domestic Production Capacity; Import Substitution Strategy